Strategic Human Resource Planning and Workforce Demographics: A Quantitative Analysis - Yadav Prasad Pokharel; Dr. Kriti; Dipak Mahat (Darul Yasin Al Sys, 2026)
Understanding whether employees’ perceptions of Strategic Human Resource Planning (SHRP) vary across demographic groups is important for evaluating organizational alignment with strategic human resource objectives. This study examined the relationships between workforce demographics and perceptions of SHRP in an organizational context. A quantitative survey design was employed, involving 150 respondents from various hierarchical levels. The sample was predominantly male (87.3%), with the largest proportion of respondents aged 36–45 years (32.0%). Descriptive and inferential analyses were conducted to assess variations in SHRP perceptions according to gender, age, educational qualification, job position, and work experience. Overall perceptions of SHRP were highly positive (grand mean = 4.70 on a five-point scale). Kendall’s tau-b correlation indicated no statistically significant association between work experience and SHRP perceptions (τ = .019, p = .766). Similarly, no significant differences were found according to gender (t = 1.328, p = .186), age group (F = 1.063, p = .377), educational qualification (F = 1.681, p = .157), or job position (F = 0.745, p = .527). These findings indicate that positive perceptions of SHRP were broadly consistent across the demographic groups examined, suggesting substantial workforce alignment with the organization’s strategic human resource objectives. The study contributes empirical evidence that demographic characteristics may not constitute significant sources of variation in SHRP perceptions and supports the development of organization-wide strategic human resource initiatives that engage employees across hierarchical and demographic categories.